More incidents that define process safety (John Wiley & Sons, Inc. ; American Institute of Chemical Engineers, 2020)
"More Incidents that Define Process Safety book describes over 50 incidents which have had a significant impact on the chemical industry as well as the basic elements of process safety. Each incident is presented in sufficient detail to gain an understanding of root causes for the event with a focus on lessons learned and the impact the incident had on process safety. Incidents are grouped by incident type including : reactive chemical, fires, explosions, environmental/toxic releases, and transportation incidents. The book also covers incidents from other industries that illustrate the safety management elements. The book builds on the first volume and adds incidents from China, India, Italy and Japan. Furthermore, at the time the first volume was being written, CCPS was developing a new generation of process safety management elements that were presented as risk based process safety, which are addressed in the incidents covered section"--